Porous, columnar shaped iron rich oxide synthesis for lithium-ion batteries from metallurgical grade, domestic, high carbon ferro-chromium alloys - Gülcan, Mehmet Feryat; Karahan, Billur Deniz; Gürmen, Sebahattin (Elsevier Ltd, 2022)
With this article, first time in the open literature, the synthesis, and the characterization of an anode material from a domestic, intermediate product (i.e. ferrochromium alloy) have been carried out. The presented approach sets an example for many researchers in the future, as it allows the fabrication of low carbon footprint electrodes cost-effectively without using materials that can cause serious harm to the environment during their production processes. The research consists of two steps. First, a dihydrate iron-rich oxalate in the columnar structure is attained by selectively precipitating manganese, nickel, and cobalt together with iron, from the leachate of the domestic ferrochromium alloy with sulphuric acid. Then, once the powder is calcinated in a vacuum at 180?C for 3 h, the anhydrous iron-rich oxalate (S1) powder is obtained and tested as an anode material. Moreover, the dihydrate iron-rich oxalate powder is calcinated in an argon atmosphere at 550?C for 2 h to successfully fabricate porous, columnar-shaped iron-rich oxide (S2) powder. Galvanostatic tests demonstrate that the calcination affects both the structure and the morphology, hence the electrochemical performance: After 250 cycles, S2 delivers 1034.75 mAh g-1, whilst S1 performs 725.39 mAh g-1. The characterizations reveal that the presence of Mn, Ni, Co, along with Fe, increases the cycleability by creating additional electron conductive pathways in the powder. Moreover, owing to the porosity formed as a result of the calcination in the argon atmosphere, both the mechanical tolerance of the anode against the volumetric expansion that occurs during the reaction with lithium and the electrolyte/electrode contact are improved which lead to a better cycle performance even at higher current loads.
Keywords: Green Electrode Design; High Carbon Ferrochromium; Hydrometallurgy; Lithium-Ion Battery; Low Carbon Footprint Anode